Yeha, Äthiopien: Site Management und Capacity Building - Gerlach, Iris (e-Forschungsberichte des DAI, 2023)
In addition to scientific work, the Ethiopian-German cooperation project in Yeha focuses on the infrastructural development of infrastructure for tourism. To follow this objective, various elements are jointly pursued [linked]: the elaboration of a site management plan; the restoration of the ruins; the renovation of a cafeteria; the erection of an information stand and appropriate signposting as well as the building of a site museum.